2019
DOI: 10.1093/jamia/ocz204
|View full text |Cite
|
Sign up to set email alerts
|

A combined strategy of feature selection and machine learning to identify predictors of prediabetes

Abstract: Objective To identify predictors of prediabetes using feature selection and machine learning on a nationally representative sample of the US population. Materials and Methods We analyzed n = 6346 men and women enrolled in the National Health and Nutrition Examination Survey 2013–2014. Prediabetes was defined using American Diabetes Association guidelines. The sample was randomly partitioned to training (n = 3174) and internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 39 publications
2
25
0
1
Order By: Relevance
“…This study demonstrated that the proof-of-concept ML workflow previously proposed by us [32] is viable, when applied to different research contexts with appropriate modifications, indicating a high degree of generalisability and adaptability. As the obstacles to implementing ML interventions in healthcare are widespread and systemic [62], those requiring only customarily compiled health information would offer more realistic solutions.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This study demonstrated that the proof-of-concept ML workflow previously proposed by us [32] is viable, when applied to different research contexts with appropriate modifications, indicating a high degree of generalisability and adaptability. As the obstacles to implementing ML interventions in healthcare are widespread and systemic [62], those requiring only customarily compiled health information would offer more realistic solutions.…”
Section: Discussionmentioning
confidence: 72%
“…The analytic workflow of this study was based on our previously published proof-of-study exploring predictors of prediabetes [ 32 ]. However, substantial modifications were made including analysing nutritional variables (omitted in the previous study) and excluding serum biomarkers in order to consider only those predictors which are simple, scalable and based on self-reported or easily measurable parameters.…”
Section: Methodsmentioning
confidence: 99%
“…Diagnosis of type 2 diabetes if not performed at an early stage can lead to several serious life-threatening complications [6]. Machine learning-based decision support systems for the prediction of chronic diseases [7][8][9][10][11][12] have thus gained a lot of attention for better prognosis/diagnosis support to health professionals and public health [13]. Several research efforts have been proposed in the literature for using machine learning classification algorithms to predict the prevalence of type 2 diabetes based on different risk factors .…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the selected studies might not be sufficient to reflect an entire trend of ML applications in the endocrinology field, but it can provide practical examples for understanding the utility of ML algorithms applied to various fields of endocrine researches. The details of the reviewed studies are summarized in Table 2 [4][5][6][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. www.…”
Section: Machine Learning Applications In Endocrinology and Metabolismmentioning
confidence: 99%